2015
DOI: 10.1140/epje/i2015-15067-6
|View full text |Cite
|
Sign up to set email alerts
|

Foam-improved oil recovery: Modelling the effect of an increase in injection pressure

Abstract: Abstract.A model, called pressure-driven growth, is analysed for propagation of a foam front through an oil reservoir during improved oil recovery using foam. Numerical simulations of the model predict, not only the distance over which the foam front propagates, but also the instantaneous front shape. A particular case is studied here in which the pressure used to drive the foam along is suddenly increased at a certain point in time. This transiently produces a concave front shape (seen from the domain ahead o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…The unrecovered oil becomes trapped in the reservoir forming discontinuous or continuous phase in swept or unswept zones of the reservoirs, respectively [ Grassia et al ., ; Sahimi , ]. The amount of trapped oil and the size of the trapped blobs depend on a variety of parameters including (but not limited to) wettability, injection rate, physical and chemical properties of the displacing and displaced fluid, presence of heterogeneity, pore size distribution, the pore‐to‐throat ratio (aspect ratio), and the topology of the pore networks [ Joekar ‐ Niasar et al ., ; Joekar‐Niasar , ; Mas‐Hernandez et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…The unrecovered oil becomes trapped in the reservoir forming discontinuous or continuous phase in swept or unswept zones of the reservoirs, respectively [ Grassia et al ., ; Sahimi , ]. The amount of trapped oil and the size of the trapped blobs depend on a variety of parameters including (but not limited to) wettability, injection rate, physical and chemical properties of the displacing and displaced fluid, presence of heterogeneity, pore size distribution, the pore‐to‐throat ratio (aspect ratio), and the topology of the pore networks [ Joekar ‐ Niasar et al ., ; Joekar‐Niasar , ; Mas‐Hernandez et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…Sometimes however (e.g. if one if trying to implement the equations numerically) it is simpler to set the initial s D value to a small non-zero value [13,18] (e.g.…”
Section: Governing Equations: Pressure-driven Growth With Anisotropymentioning
confidence: 99%
“…Previous studies in the case of homogeneous permeability [11,13,14] have demonstrated that the system attains a state in which the 'apparent' horizontal velocity is uniform with position. 'Apparent' horizontal velocity is the difference in horizontal displacement per difference in time between two points on the front at the same vertical height at two different times.…”
Section: Modifying Velocity For Concavities and Regridding The Frontmentioning
confidence: 99%
“…We have studied previously the displacement of foam within a homogeneous reservoir [11] (revisiting a model of Shan and Rossen [12]), and also two additional cases, one where the injection pressure is increased part way through the process and one taking into account the effect of surfactant slumping due to gravity [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation